Land Contestation and Identity: Agrarian Conflict Between Maluku Indigenous Communities and State Authorities in a Sociological Perspective - Leiwakabessy, Jeffry Ernest Marthen (Universitas Pattimura, 2024)
This article examines the agrarian conflict between indigenous communities in Maluku and state authorities, with a particular focus on the dispute between the indigenous community of Negeri Laha and the Indonesian Air Force. Utilizing a sociological perspective, the study aims to uncover the root causes, processes, and resolution mechanisms of agrarian conflict, while proposing preventative strategies that emphasize the role of indigenous communities in land governance. Through qualitative methods—including in-depth interviews, field observations, and document analysis of legal decisions and scholarly literature—the study reveals that contested land ownership, state-led strategic projects, and the marginalization of customary land rights are key triggers of conflict. The findings suggest that inclusive dialogue, recognition of indigenous land rights, and the use of customary conflict resolution mechanisms are vital in achieving sustainable peace. The case of Negeri Laha serves as a valuable reference for resolving similar conflicts in other regions of Indonesia. The novelty of this research lies in its integration of legal, sociocultural, and conflict resolution dimensions, providing a contextual model that links land contestation with identity politics and state power. This article contributes to the development of social sciences and humanities by offering policy-oriented insights into managing agrarian conflicts through participatory and non-violent approaches grounded in local wisdom.